INCREASE OF SHELF LIFE STABILITY AND KINETICS STUDY OF TYPE 1 BROWN RICE MILK THROUGH ADDITION OF ALGINATE EXTRACT FROM Sargassum binderi - Rais Nur Latifah; Cecep Setiawan (Food ScienTech Journal, 2019)
Brown rice milk obtained from rice is used for lactose intolerance and as a lower fat milk choice. This research aimed to use the sodium alginate extracted from Sargassum binderi as a stabilizer and degradation of brown rice milk. Sargassum binderi seaweed was taken from Sayang Heulang beach, Pameungpeuk Garut, West Java. Kinetics study to improve stability and shelf life of type I brown rice milk with analysis of brown rice milk dye degradation, effect of addition of alginate to the pH brown rice milk and effect of addition alginate to the stability of brown rice milk. Result of this research showed that pH value of the composition of brown rice milk from various variations of the addition alginate was constant until the 15 days to various compositions of adding alginate to milk. Then, the sedimentation rate of the effect addition alginate was in the first order. The addition of 1.2% alginate had the lowest constant deposition rate at 0,0171. The constant rate of deposition brown rice milk samples with the addition of 1.2% alginate was 0.0022, this considered the best milk sample because it successfully suppressed the degradation rate of dyes up to 95.79% compared to those without the alginate addition. The number of microbes that appear in milk samples had not exceeded the maximum limit of microbial contamination.